E0243 A Study on epidemiological trend of elderly hypertension in Beijing. (17th November 2010) - ALi-Na,; Zhe, Tang; Xiao-Ling, Zhao; Shao-Chen, Guan; Fei, Sun; Hong-Jun, Liu; Xiao-Guang, Wu; Li-Jun, Diao
Abstract : Object: To explore the epidemiological trend of elderly hypertension, so as to provide basis for prevention of hypertension. Method: A group of 2832, 1828, 2277 elderly residents aged ≥60 in Beijing were chosen into this study in the year 2000, 2004, 2007 by well-established statistical sampling techniques such as cluster, stratification and random selection, and epidemiological trend of elderly hypertension was analysed by x 2 analysis. Result: The prevalence rate (69.2%, 61.9%, 56.0%) of hypertension and the control rate (22.6%, 16.7%, 21.5%) lowered annually, and awareness rate (43.7%, 55.8%, 57.6%) of treatment elevated annually. There was no rising in the control rate of male (26.2%, 16.7%, 20.8%), less older (28.0%, 18.4%, 21.0%) and rural (19.5%, 9.6%, 13.4%). Conclusion: The results indicate that the prevalence of hypertension is high in the elderly rural people, while the rates of awareness, treatment and control are low. It suggests that effective public measures need to be developed to improve the prevention and control of hypertension.